An evaluation of the Movement ABC-2 Test for use in Italy: A comparison of data from Italy and the UK. (January 2019) - Zoia, Stefania; Biancotto, Marina; Guicciardi, Marco; Lecis, Romina; Lucidi, Fabio; Pelamatti, Giovanna M.; Carrozzi, Marco; Skabar, Aldo; Sugden, David A.; Barnett, Anna L.; Henderson, Sheila E.
Highlights: For the first time, the Italian and British raw scores of the MABC-2 Test were compared. This study starts to examine the properties of the MABC-2 Test for use in Italy. The Italian norms support the good structural validity of the MABC-2 Test. Abstract: Background: The standardized test within the Movement Assessment Battery for Children-2nd edition (MABC-2) is used worldwide to assess motor problems in children. Ideally, any country using a test developed in another country should produce national norms to ensure that it functions effectively in the new context. Aim: The first objective of this study was to explore the differences in motor performance between Italian and British children. The second was to examine the structural validity of the test for the Italian sample. Method: A total of 718 Italian (IT) and 765 British (UK) children, aged 3–10 years, were individually tested on the age-appropriate items of the MABC-2 Test. Results: Developmental trends emerged on every task and differences between IT and UK children were obtained on 11 of 27 task comparisons. Interactions between age and country indicated that differences were not consistently in favor of one culture. Confirmatory factor analysis generally supported the proposed structure of the MABC-2 Test. Conclusion: Although the differences between the IT and the UK children were relatively few, those that did emerge emphasize the need for population specific norms and suggest that cultural diversity in motor experiences should be considered when evaluating motor abilities in children.